Increasing the number of midwives is necessary but not sufficient: using global data to support the case for investment in both midwife availability and the enabling work environment in low- and middle-income countries - Andrea Nove; Martin Boyce; Sarah Neal; Caroline S. E. Homer; Tina Lavender; Zoë Matthews; Soo Downe (BMC, 2024)
Abstract Background Most countries are off-track to achieve global maternal and newborn health goals. Global stakeholders agree that investment in midwifery is an important element of the solution. During a global shortage of health workers, strategic decisions must be made about how to configure services to achieve the best possible outcomes with the available resources. This paper aims to assess the relationship between the strength of low- and middle-income countries' (LMICs') midwifery profession and key maternal and newborn health outcomes, and thus to prompt policy dialogue about service configuration. Methods Using the most recent available data from publicly available global databases for the period 2000-2020, we conducted an ecological study to examine the association between the number of midwives per 10,000 population and: (i) maternal mortality, (ii) neonatal mortality, and (iii) caesarean birth rate in LMICs. We developed a composite measure of the strength of the midwifery profession, and examined its relationship with maternal mortality. Results In LMICs (especially low-income countries), higher availability of midwives is associated with lower maternal and neonatal mortality. In upper-middle-income countries, higher availability of midwives is associated with caesarean birth rates close to 10-15%. However, some countries achieved good outcomes without increasing midwife availability, and some have increased midwife availability and not achieved good outcomes. Similarly, while stronger midwifery service structures are associated with greater reductions in maternal mortality, this is not true in every country. Conclusions A complex web of health system factors and social determinants contribute to maternal and newborn health outcomes, but there is enough evidence from this and other studies to indicate that midwives can be a highly cost-effective element of national strategies to improve these outcomes.